O triste cristianismo e Jesus de Nazaré - Leers, Bernardino (Revista eclesiástica brasileira, 2001)
The "heavy atmosphere" of some — still persistent — traits of Brazilian Catholicism is not only the result of the hardships and miseries of a large part of the population. It is also a legacy of the Jansenist and Neo-Jansenist spirit that does not go well with the hope and thefreedom preached in the Gospels. To rediscover Jesus Christ as the Good Tidings, therefore, is to free oneself from the understandings that make us less happy as Christians.